Factors associated with quality of life among cancer patients in Sri Lanka - Rukshani, Dilka; Kahandawala, Pabasara; Jayawardana, Kasun; Karunarathne, Dilan; Galgamuwa, Lahiru S.; Kumara, Chandima; Gamage, Charuni (International Journal Of Community Medicine And Public Health, 2018)
Background: Quality of life (QOL) is individuals’ perception of their position in life in the context of the culture and value systems in which they live and in relation to their goals, expectations, standards and concerns. It is an effective modern method of early identification of chronic incurable disease patients. This study was designed to determine the level and the possible contributory factors of quality of life in heterogeneous groups of cancer patients in Sri Lanka. Methods: This study was conducted at National Cancer Institute of Sri Lanka. WHOQOL-BREF questionnaire was used to assess QOL of cancer patients. Multivariate linear regression model was used to evaluate the associations of demographic variables, clinical characteristics, and social support status with the quality of life measures. Results: 167 of cancer patients were participated. The mean overall QOL score was 53.07±SD 12.68. Higher QOL was associated with patients who were married, higher educated, employed, had good family support and longer duration of illness. Significantly lower QOL was found in those who involved on radiotherapy treatments and feeling alone. Marital status, education status, comorbidity, family support and feeling alone were identified as predictors for QOL among the study group. Conclusions: The overall QOL score was considerably low in our study. Continuous family support and good education may significantly improve the QOL of cancer patients. Psychosocial and awareness programs to the family members and neighbours should be implemented to enhance the quality of life of cancer patients.